Inhibition of pan-Aurora kinase attenuates evoked and ongoing pain in nerve injured rats via regulating KIF17-NR2B mediated signaling - Uniyal A.; Akhilesh; Singh Rathore A.; Kumari Keshri P.; Pratap Singh S.; Singh S.; Tiwari V. (My University, 2025)
Kinesins (KIF's) are the motor proteins which are recently reported to be involved in the trafficking of nociceptors leading to chronic pain. Aurora kinases are known to be involved in the regulation of KIF proteins which are associated with the activation of N-methyl-D-aspartate (NMDA) receptors. Here, we investigated the effect of tozasertib, a pan-Aurora kinase inhibitor, on nerve injury-induced evoked and chronic ongoing pain in rats and the involvement of kinesin family member 17 (KIF17) and NMDA receptor subtype 2B (NR2B) crosstalk in the same. Rats with chronic constriction injury showed a significantly decreased pain threshold in a battery of pain behavioural assays. We found that tozasertib [10, 20, and 40 mg/kg intraperitoneally (i.p.)] treatment showed a significant and dose-dependent inhibition of both evoked and chronic ongoing pain in rats with nerve injury. Tozasertib (40 mg/kg i.p.) and gabapentin (30 mg/kg i.p.) treatment significantly inhibits spontaneous ongoing pain in nerve injured rats but did not produce any place preference behaviour in healthy naïve rats pointing towards their non-addictive analgesic potential. Moreover, tozasertib (10, 20, and 40 mg/kg i.p.) and gabapentin (30 mg/kg i.p.) treatment did not altered the normal pain threshold in healthy naïve rats and didn't produce central nervous system associated side effects as well. Western blotting and reverse transcription polymerase chain reaction studies suggested enhanced expressions of NR2B and KIF-17 along with increased nuclear factor kappa β (NFkβ), tumour necrosis factor-α (TNF-α), interleukin 1β (IL-1β), and interleukin 6 (IL-6) levels in dorsal root ganglion (DRG) and spinal cord of nerve injured rats which was significantly attenuated on treatment with different does of Tozasertib. Findings from the current study suggests that inhibition of pan-Aurora kinase decreased KIF-17 mediated NR2B activation which further leads to significant inhibition of evoked and chronic ongoing pain in nerve-injured rats. © 2022 Elsevier B.V.